Euclid's Elements in Hebrew Garb : Critical Editions of the Translation by Moses Ibn Tibbon and the Translation Ascribed to Rabbi Jacob, with an Introduction and Glossary, Volume Two: Books III-VI - Elior, Ofer, (Études sur le judaïsme médiéval ;, 2024)
Euclid's Elements is one of the canonical texts that shaped our cultural heritage. It was translated from Greek to Arabic and from Arabic into Hebrew and Latin. There is little agreement about the textual history of the Arabic translations. The present book offers for the first time a critical edition of two Hebrew translations of Books III-VI, by Moses Ibn Tibbon and by "Rabbi Jacob". A serious attempt is made to learn from the Hebrew translations also on the history of the Arabic text. The edition of Ibn Tibbon's translation is accompanied by an Arabic text which was probably its source. Rabbi Jacob's translation is compared to an Arabic preserved in ms. BULAC Ara. 606, and very close to one of the translation's primary sources.